Natural genetic variation in lycopene epsilon cyclase tapped for maize biofortification - Harjes, Carlos E.; Rocheford, Torbert R.; Bai, Ling; Brutnell, Thomas R.; Kandianis, Catherine Bermudez; Sowinski, Stephen G.; Stapleton, Ann E.; Vallabhaneni, Ratnakar; Williams, Mark; Wurtzel, Eleanore T.; Yan, Jianbing; Buckler, Edward S. (International Food Policy Research Institute, 2008)
Maize is the dominant subsistence crop in much of sub-Saharan Africa and the Americas, where 17 to 30 percent of children under age 5 are vitamin A deficient. Diet diversification, food fortification, and supplementation have all been used to combat dietary micronutrient deficiencies. However, diet diversification is often limited by crop seasonality, expense, and low bioavailability of green leafy plant carotenoids. In addition, poor infrastructure has limited widespread use of direct vitamin supplementation. Perhaps the most feasible approach, therefore, is biofortification, a process by which staple crops are purposefully bred for higher nutritional density. Biofortified foods could potentially be an inexpensive, locally adaptable, and long?term solution to diet deficiencies.